THE PROBLEM OF ECONOMIC AND BUSINESS DEVELOPMENT IN NORTH LIMA - Wong Cabanillas, Francisco Javier (2016)
Currently there are studies -from various approaches- that present and recognize the importance of socio-economic and business growth and development in the districts identified as Lima Norte (Ancon, Carabayllo, Comas, Independencia, Los Olivos, Puente Piedra, San Martin de Porres and Santa Rosa). These approaches come from the economy (growth); from the social (diversification and citizen mobility); from culture (provincial presence in the area); from the education (the levels and professionalism); from the organizational (political and business); from marketing and psychology (identification and local presence). And all have been manifested in studies from the academic and business world. By demographic description and the social, economic, political, organizational, cultural, educational and health characteristics, the nuances of its recent past are externalized which are reflected according to the place of origin of the citizens responsible of that development or its predecessors - parents and family in general - which make a difference but at the same time, provide experiences, stories and traditions that are reflected in this development.